Method for evaluating crystal diameter for a plurality of crystal materials based on average power attenuation of ultrasonic coder waves

The use of ultrasonic coda waves for measuring average power attenuation addresses the inefficiencies of existing methods, enabling accurate and efficient evaluation of crystal grain diameter in nickel base alloys, particularly in turbine disks.

JP2025016327AActive Publication Date: 2025-01-31BEIHANG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024008263
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-21
Filing Date
2024-01-23
Publication Date
2025-01-31
Estimated Expiration
2044-01-23

AI Technical Summary

Technical Problem

Current methods for evaluating crystal grain diameter in nickel base high-temperature alloys, such as those used in turbine disks, are either destructive and costly or inefficient and limited in non-destructive techniques, particularly with ultrasonic methods that struggle with accuracy and efficiency in detecting uneven grain sizes.

Method used

A method utilizing ultrasonic coda waves to measure the average power attenuation for evaluating crystal diameter, involving signal excitation, pre-processing, and logarithmic modeling to determine the average crystal diameter with high efficiency and accuracy.

Benefits of technology

The method accurately and efficiently determines the average crystal diameter of multiple crystal materials, overcoming limitations of conventional ultrasonic techniques by using coda waves to capture wide-range measurements with high sensitivity and precision.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016327000001_ABST
    Figure 2025016327000001_ABST
Patent Text Reader

Abstract

To provide a method for a crystal diameter for a plurality of crystal materials based on attenuation of average power of ultrasonic coder waves.SOLUTION: A method includes: manufacturing samples having the same thickness as a crystal materia to be detected to identify forms and parameters that excite signals, and constructing a detection system for an average crystal diameter of the crystal material; exciting and receiving an ultrasonic signal for each of the samples having different average crystal diameters to perform preceding processing of bandpass filtering; selecting the signals to be used for a coder wave time window and a reference time window to acquire average power for each signal to calculate average power attenuation of coder waves on the basis of a time difference; creating a logarithmic line model between an average size of crystallites and average power attenuation of the coder waves for each sample on the basis of an equivalent attenuation coefficient model; and collecting the signals for the crystal materials to be detected and having an unknown crystal diameter to acquire the average power attenuation of the coder waves to identify an average crystal diameter of the crystal material on the basis of the logarithmic line model.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a technical field of detecting the crystal sizes of a plurality of crystalline materials without damaging them, and in particular to a method for evaluating the crystal sizes of a plurality of crystalline materials based on the attenuation of the average power of ultrasonic coda waves. [Background technology]

[0002] Nickel-based high temperature alloys are widely used in modern advanced aviation engines as a representative main material for manufacturing core parts such as turbine disks in advanced aviation engines. Currently, large-sized high temperature alloy blanks used in turbine disks are prone to uneven grain structure during processing due to the limitations of processing technology, and some grains are coarse, resulting in reduced tensile strength and fatigue resistance, and inconsistent mechanical properties. In serious cases, the product may fail and be scrapped, which will have a significant impact on the integrity and reliability of the equipment. Therefore, developing an efficient and accurate grain size evaluation method for alloy blanks is helpful in achieving stable quality of high temperature alloy turbine disks under mass production conditions, and has important engineering and practical value.

[0003] Currently, the most commonly used methods for detecting grain size are mainly divided into two categories: destructive and non-destructive. In destructive testing techniques such as optical metallography and backscattered electron diffraction, a small test piece is cut from the sample to be tested, and the grain structure characteristics of the surface of the test piece are photographed by an optical or electron microscope to evaluate the average grain size. Although destructive testing methods can characterize the grain microstructure with high accuracy, they often cannot cut the sample because they detect the actual structure in an engineering manner, and their application range is limited due to the high detection costs. This is why non-destructive detection techniques such as X-ray testing and solid wave ultrasonic testing have become highly developed. X-ray testing uses the attenuation and scattering characteristics of the interaction between X-rays and the material when they propagate through the test object to observe the internal grain microstructure of the test object, but the equipment is expensive, so if it is used for a long period of time as necessary, the measurement becomes inefficient.

[0004] Detection methods based on body wave ultrasound generate ultrasound waves in materials, interact with the microstructure inside the material, analyze the characteristics of the waves, and evaluate the material properties. The selected body wave ultrasound waveform characteristics mainly include wave speed characteristics, backscattering characteristics, and attenuation characteristics. Regarding the principle of wave speed characteristics, it can be said that the sound speed is calculated from the thickness of the measurement object and the time delay between two echoes, and the average grain size is evaluated. The relationship between wave speed and grain size is not monotonic within a certain grain size range, and the sensitivity to some metal materials is low, so an accurate measurement system is required for detection. Regarding backscattering characteristics, it focuses on the numerous scattered waves generated by the interaction between ultrasound and the grain boundary surface where the acoustic impedance is mismatched inside the material, and appears as a noise-like interference signal between the wave and the echo signal in the time domain signal. However, the acquisition of backscattering signals is inefficient because it requires multiple spatial samplings and averaging. Attenuation characteristics refer to the characteristic that the longer the propagation distance of ultrasound in the process of propagation through a material, the weaker the energy attached to it becomes. This allows the amplitude of the surface echo and each bottom wave in the pulse-echo method to be gradually decreased to evaluate the particle size, and has good stability. However, due to the limitations of body wave ultrasound, only the average particle size in a single channel can be detected, and spatially dense sampling is required for large structures, which is inefficient and may lead to missed detection of local particle abnormalities.

[0005] Coda waves are formed by multiple scattering of ultrasonic waves in heterogeneous media and appear as tails behind the waves directly. Coda waves are responsible for repeatedly sampling the space on a longer time scale than body waves, so they are more sensitive to the characteristics of fine grain structures and can achieve a wide range of measurements with a single measurement at a single sensor location. Therefore, it is very urgent and very important to find a method for evaluating the grain size of polycrystalline materials based on the average power attenuation of ultrasonic wake waves, combining the advantages of detecting ultrasonic attenuation characteristics and coda waves to efficiently achieve average grain size evaluation. Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention provides a method for evaluating the crystal size of a plurality of crystalline materials based on the attenuation of the average power of ultrasonic coda waves, in contrast to the defects in the above-mentioned prior art. [Means for solving the problem]

[0007] First, a number of samples having the same thickness as the multiple crystalline materials to be detected are prepared, and the form and parameters of exciting the signal are identified. Then, a detection system for the average crystal size of the multiple crystalline materials is installed. For samples having different average crystal sizes, ultrasonic signals are excited and received, and a preliminary process of bandpass filtering is performed. The signals of the coda wave time window and the reference time window are selected, and the average power is obtained, respectively, and the average power attenuation of the coda wave is calculated based on the time difference. Based on the equivalent attenuation coefficient model, a logarithmic model is created between the average crystal size of the sample and the average power attenuation of the coda wave. The signals of the multiple crystalline materials to be detected and the crystal sizes of which are unknown are collected and filtered, and then the average power attenuation of the corresponding coda wave is obtained, and the average crystal sizes of the multiple crystalline materials are identified based on the logarithmic model. Compared with the conventional body wave method, the present invention has a high detection efficiency and is relatively easy, has strong practicality, and provides more accurate detection results.

[0008] Specifically, the method for evaluating the crystal sizes of a plurality of crystalline materials based on the attenuation of the average power of ultrasonic coda waves provided by the present invention includes: Step S1: preparing a number of samples having the same thickness as the multiple crystal materials to be detected, identifying the form and parameters for exciting the signal, and constructing a detection system for the average crystal size of the multiple crystal materials; Step S2, which performs a preliminary process of exciting and receiving ultrasonic signals for samples having different average crystal sizes and band-pass filtering the collected ultrasonic signals; Step S3 of selecting JPEG2025016327000002.jpg7170, obtaining the average power of each, and calculating the average power attenuation of the coda wave based on the time difference; JPEG2025016327000003.jpg15170JPEG2025016327000004.jpg7170Among them, step S31 in which the coda wave average power P(t) indicates the energy state of the coda wave portion of the ultrasonic signal at timing t; JPEG2025016327000005.jpg28170JPEG2025016327000006.jpg15170JPEG2025016327000007.jpg33170The attenuation coefficient model is calculated as follows: Step S33 showing JPEG2025016327000008.jpg11170JPEG2025016327000009.jpg4170; Step S3, the acquired coda wave time window and the reference time window are located in the coda wave portion and the fundamental wave portion of the ultrasonic signal, and the selection of the coda wave portion is based on the arrival time of the double shortest boundary wave, and the coda wave signal in the selected coda wave time window has a high signal-to-noise ratio; JPEG2025016327000010.jpg10170JPEG2025016327000011.jpg6170, where θ1 and θ2 respectively represent the first and second fitting parameters of the model; Step S4 of evaluating the model first fitting parameters and the model second fitting parameters by the least squares method; The average crystal size detection system for the plurality of crystal materials collects and filters ultrasonic signals of the plurality of crystal materials having an unknown crystal size to be detected, and the obtained signal is filtered in step S3. JPEG2025016327000012.jpg11170JPEG2025016327000013.jpg7170

[0009] Preferably, step S1 includes a step S11 of producing a number of samples having the same chemical composition but different average crystal sizes based on the material component information of the plurality of crystal materials to be detected, and cutting the samples into plate-shaped samples having the same thickness as the plurality of crystal materials to be detected; Step S12, in which the excitation source for exciting the ultrasonic signal is a Hanning window modulated sinusoidal pulse having a single center frequency, and the ultrasonic signal frequency is selected based on the elastic property and thickness information of the multiple crystalline materials to be detected; Step S13: outputting ultrasonic waves through a single channel of an arbitrary function generator, and forming two output ends through a T-joint, of which the first output end is connected to a high-voltage power amplifier, amplified and then transmitted to an excitation ultrasonic transducer wafer, and the second output end is directly transmitted to an excitation channel of a mixed signal oscilloscope; Step S14: for each sample, a pair of excitation transducer wafers and receiving transducer wafers having the same center frequency are closely arranged and fixed at the center of the surface of the sample; For each excitation, the method includes step S15 of collecting the ultrasonic signal propagating through the sample by the receiving transducer wafer based on the triggering signal received by the triggering channel, and transmitting the ultrasonic signal to the collecting channel of the mixed signal oscilloscope.

[0010] Preferably, step S2 specifically comprises: A step S21 of randomly cutting out and sampling each sample to obtain an actual crystal size; Step S22: detecting each sample using a pulsed wave format, the transducer wafer generating an excitation ultrasonic signal in the sample, and the receiving transducer wafer receiving the ultrasonic signal transmitted in the sample; Steps S21 and S22 are repeatedly performed until ultrasonic signals corresponding to samples having different average crystal sizes are obtained, and a preliminary step S23 is included in which the ultrasonic signals are band-pass filtered.

[0011] Preferably, the signal received by the receiving transducer wafer in step S2 is an average value of 128 consecutive signal samples taken by a mixed signal oscilloscope.

[0012] Preferably, in step S2, a pulsed wave form is adopted to detect the ultrasonic signal in each sample.

[0013] Preferably, in step S21, the actual crystal size d of the sample is quantified via an electron backscatter diffraction technique.

[0014] Preferably, in step S1, the average crystal size detection system for the plurality of crystal materials includes an arbitrary function generator, a T-joint, a high-voltage power amplifier, an excitation transducer wafer, a receiving transducer wafer, a mixed signal oscilloscope and an upper controller.

[0015] The single channel of the arbitrary function generator outputs ultrasonic waves and transmits them to the Tee joint, the Tee joint has two output terminals, the first output terminal is connected to a high-voltage power amplifier, amplified and then transmitted to an excitation ultrasonic transducer wafer, and the second output terminal is directly transmitted to a trigger channel of a mixed signal oscilloscope, the excitation transducer wafer is for generating an excitation ultrasonic signal, and the receiving transducer wafer receives the transmitted ultrasonic signal and transmits the ultrasonic signal to the upper controller. Effect of the Invention

[0016] (1) The method for evaluating the crystal size of multiple crystalline materials based on the attenuation of the average power of ultrasonic coda waves provided by the present invention is based on the theory of ultrasonic scattering, and based on the influence of the microscopic structure of multiple crystalline materials on the properties of ultrasonic waves, selects a coda wave time window and a reference time window, respectively, obtains the average crystal size of the material and the corresponding average power attenuation of the coda wave, and calculates the sample average The average power attenuation of the coda waves of the multiple crystalline materials of JPEG2025016327000014.jpg4170 is obtained, and the average crystal size of the multiple crystalline materials of the detection target is specified based on the logarithmic model. This detection method can accurately obtain the average crystal size of the multiple crystalline materials without destroying the multiple crystalline materials of the destructive detection target. This method incorporates the advantages of ultrasonic attenuation characteristics and coda wave detection, and quantifies and evaluates the average crystal size of the multiple crystalline materials using the average power attenuation of the coda waves, which has high detection efficiency and excellent robustness in surveying.

[0017] (2) The method for evaluating the crystal size of multiple crystalline materials based on the attenuation of the average power of ultrasonic coda waves proposed by the present invention, compared with the conventional ultrasonic method using the attenuation of direct waves, uses the attenuation of the coda wave part to evaluate ultrasonic waves and materials, so that it is possible to evaluate crystal size information over a wide range at a single sensor position with a single measurement, and has a higher detection efficiency. Since the energy state of ultrasonic waves is indicated using the average power, it is difficult to obtain the width value of ultrasonic waves propagating through highly non-uniform structures, and the disadvantage of being easily interfered with can be avoided, and a more robust evaluation of crystal size can be achieved. The true crystal size measured by electron backscatter diffraction technology is included in 99% of the confidence interval for predicting the obtained crystal size, so it is considered to have a high degree of prediction certainty. [Brief description of the drawings]

[0018] Other features, objects and advantages of the present invention will become more apparent from the following non-limiting detailed description of the embodiments with reference to the drawings. [Figure 1] 1 is a flowchart showing a method for evaluating the crystal sizes of multiple crystalline materials based on the attenuation of the average power of ultrasonic coda waves according to the present invention. [Diagram 2] FIG. 1 is a schematic diagram showing an average crystal size detection system and flow of multiple crystal materials according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic diagram showing sample size and transducer placement according to an embodiment of the present invention. [Figure 4] 10A-10C contrast waveforms filtered in a reference time window and a coda time window for different samples measured according to an embodiment of the present invention. [Diagram 5] FIG. 11 is a diagram showing a comparison of experimental values ​​of a sample and a plurality of crystalline materials to be detected with respect to the logarithmic relationship between the sample average crystal size and the average power attenuation of coda waves, which is created by employing logarithmic fitting according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present application will be described in more detail below based on the embodiments with accompanying drawings. It is to be understood that the specific embodiments described herein are merely for interpreting the present invention and are not intended to limit the present invention. For the sake of convenience, only the parts related to the present invention are shown in the drawings.

[0020] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present application will now be described in detail with reference to the accompanying drawings, in which: FIG.

[0021] The present invention provides a method for evaluating the crystal size of a multi-crystalline material based on the attenuation of the average power of ultrasonic coda waves, which includes the following steps, as shown in FIG. 1 .

[0022] Step S1 is to prepare a number of samples having the same thickness as the multiple crystal materials to be detected, identify the form and parameters for exciting the signal, and construct a detection system for the average crystal diameter of the multiple crystal materials.

[0023] The system for detecting the average crystal size of multiple crystal materials includes an arbitrary function generator, a BNC T-joint, a high-voltage power amplifier, an excitation transducer wafer, a receiving transducer wafer, a mixed signal oscilloscope, and a host controller. An ultrasonic wave is output by a single channel of the arbitrary function generator and transmitted to the T-joint. The T-joint has two output terminals, the first output terminal of which is connected to the high-voltage power amplifier and amplified before being transmitted to the transducer wafer. The second output terminal is directly transmitted to the stimulation channel of the mixed signal oscilloscope. The excitation transducer wafer is for generating an excitation ultrasonic signal, and the receiving transducer receives the transmitted ultrasonic signal and transmits the ultrasonic signal to the host controller. In this embodiment, the host controller is a computer.

[0024] Step S1 specifically includes the following sub-steps. In step S11, based on the material component information of the multiple crystalline materials (also called polycrystalline metal materials or polycrystalline metal structures) to be detected, process parameters in the heat treatment are adjusted to produce several samples having the same chemical components but different average crystal sizes, and the samples are cut into plate-shaped samples having a thickness matching that of the multiple crystalline materials to be detected. In step S12, the excitation source for exciting the ultrasonic signal is a Hanning window modulated sine wave pulse having a single center frequency, and the ultrasonic signal frequency is selected based on the elastic properties and thickness information of the multiple crystalline materials to be detected that are known in advance, so that the sensitivity and resolution of the crystal size measurement are balanced. Step S13: output ultrasonic wave through single channel of arbitrary function generator, and form two output ends by BNC T-joint, among which, the first output end is connected to high voltage power amplifier, and is amplified and then transmitted to excitation ultrasonic transducer wafer, and the second output end is directly transmitted to the stimulation channel of mixed signal oscilloscope. Step S14 is to prepare a pair of excitation transducer wafer and receiving transducer wafer having the same center frequency for each sample, place them closely together, and fix them to the center of the sample surface by glue. Step S15: for each excitation, based on the triggering signal received by the triggering channel, the ultrasonic signal propagating through the sample is collected by the receiving transducer wafer, and transmitted to the collecting channel of the mixed signal oscilloscope for further data processing.

[0025] Step S2 performs a preliminary process of exciting and receiving ultrasonic signals for samples having different average crystal sizes, and band-pass filtering the collected ultrasonic signals. This step specifically includes the following sub-steps: Step S21: while randomly cutting out and sampling each sample, obtain the actual crystal size, that is, through the electron backscatter diffraction technique, and quantify the true crystal size for reference. Step S22 detects each sample in the form of a pulse wave, the transducer wafer excites the sample to generate an excitation ultrasonic signal, and the receiving transducer wafer receives the ultrasonic signal transmitted in the sample. The ultrasonic signal received by the receiving transducer wafer is the average value of the mixed signal oscilloscope continuously collecting the signal 128 times. Step S23 repeats steps S21 and S22 until ultrasonic signals corresponding to samples with different average crystal sizes are obtained, and a preliminary process of band-pass filtering the ultrasonic signals is performed to eliminate frequency components that are not related to the evaluation of the crystal size.

[0026] JPEG2025016327000015.jpg7170 select the ultrasonic signal to be transmitted, respectively obtain the average power of both, and calculate the average power attenuation of the coda wave based on the time difference. This step specifically includes the following sub-steps: JPEG2025016327000016.jpg16170JPEG2025016327000017.jpg7170The coda wave average power P(t) indicates the energy state of the coda wave part of the ultrasonic signal at the timing t. The selection of the coda wave part is preferably based on the striking time of the double shortest boundary wave. Moreover, the coda wave signal must have a relatively high signal-to-noise ratio within the selected time window. JPEG2025016327000018.jpg22170 is calculated as follows: JPEG2025016327000019.jpg15170JPEG2025016327000020.jpg33170The equivalent attenuation coefficient model of power is calculated as follows: JPEG2025016327000021.jpg8170JPEG2025016327000022.jpg11170

[0027] The coda wave time window and the reference time window acquired in step S3 are located in the coda wave portion and the fundamental wave portion of the ultrasonic signal, respectively. The selection of the coda wave portion is based on the arrival time of the double shortest boundary wave, and the coda wave signal in the selected coda wave time window has a high signal-to-noise ratio.

[0028] Step S4: Based on the equivalent attenuation coefficient model of the average power of the coda wave, the sample average JPEG2025016327000023.jpg5170JPEG2025016327000024.jpg6170Of these, θ1 and θ2 respectively indicate the model first fitting parameter and the model second fitting parameter, and both are evaluated by the least squares method.

[0029] In step S4, the model first fitting parameters and the model second fitting parameters are evaluated based on the least squares method.

[0030] Step S5 is to collect ultrasonic signals of a plurality of crystalline materials which are the detection target and have unknown crystal sizes, and to collect ultrasonic signals of a plurality of crystalline materials which are the detection target and have unknown crystal sizes in step S3. JPEG2025016327000025.jpg10170JPEG2025016327000026.jpg7170

[0031] The present invention will be described in more detail below based on an embodiment for detecting the crystal sizes of specific crystal materials, and the overall flow is shown in FIG.

[0032] Step S1 is to prepare five samples (respectively designated as #1, #2, #3, #4, and #5) having the same composition as the sample to be detected, which is made of high-temperature nickel alloy and has the model number GH742. The samples and the sample to be detected are all 5 mm thick, 190 mm long, and 100 mm wide. As shown in Figure 3, the specific process is as follows: In step S11, the five samples have different average crystal sizes because the dissolution temperatures and times employed in the heat treatment process are different. In step S12, the excitation signal is a Hanning window modulated sine pulse with a center frequency of 5 MHz and a period of 3.5. Step S13: The excitation signal generated by the arbitrary function generator (Tektronix, AFG 31022) is output through two circuits formed by a BNC T-joint, of which the first output terminal is connected to a high voltage power amplifier (Aigtek, ATA-4012) and amplified to a peak value of 80V, which is then transmitted to a transducer wafer (Siansonic, with a center frequency of 5MHz), and the second output terminal is directly transmitted to the excitation channel of a mixed signal oscilloscope (Tektronix, MDO3104). In step S14, the exciting transducer wafer and the receiving transducer wafer (Siansonic, center frequency 5 MHz), both of which are circular and have a diameter of 10 mm, are closely placed and fixed at the center of the sample surface with an adhesive such as glue, as shown in FIG. 3. Step S15: for each excitation, according to the triggering signal received by the triggering channel, the ultrasonic signal propagating through the sample is collected by the receiving transducer wafer, and transmitted to the collecting channel of the mixed signal oscilloscope.

[0033] In step S2, each sample is randomly cut and sampled, and a microstructure photograph of the sample is taken through electron backscatter diffraction technology, and the experimental value of the log-normal distribution of crystal size is obtained through the equivalent diameter method, and the log-normal distribution average value of the crystal size is selected as the true crystal size. Ultrasonic signals are excited and received for samples with different average crystal sizes. The collected signal is averaged in the time domain by continuously collecting signals of only 128 orders in advance inside the mixed signal oscilloscope, and then input into the upper controller, where it is subjected to pre-processing by bandpass filtering with a passband of [0.1MHz, 10MHz] through a wavelet filter.

[0034] Step S3 is the ultrasonic signal selected for five samples, with the coda wave time window being [66.22μs, 77.22μs] and the reference time window being [0.5μs, 40μs], as shown in FIG. 4. The characteristic that is sensitive to the crystallite size is the attenuation of the data coda wave part of the received signal. Also, different initial contact conditions will change the energy finally transmitted to the structure, thereby affecting the coda wave part of the signal and the reference window part of the signal. Since the attenuation coefficient is a relative value, the influence of the contact condition on the signal can be minimized. In this case, the change in the attenuation coefficient between different samples is, to a certain extent, due to the different crystallite sizes. The average power is obtained for each sample and the corresponding signal time window, and the average power attenuation of the coda wave is calculated based on the time difference according to formula (3).

[0035] Step S4, perform log-linear fitting on the experimental results as shown in Eq. (4) and Fig. 5. JPEG2025016327000027.jpg4170. The filled circles indicate the relationship between the reference average crystal size quantified by electron backscatter diffraction technology and the average power attenuation of the coda wave for each sample, and the solid lines indicate the results of fitting via the log-linear least squares method, with the first fitting parameter θ1 = 5.5343 and the second fitting parameter θ2 = 0.8732. As the average crystal size increases, the average power attenuation of the coda wave increases log-linearly.

[0036] Step S5 collects and filters the signals of the unknown crystal sizes of the crystalline materials to be detected; step S3 obtains the average power attenuation of the coda waves corresponding to the crystalline materials to be detected; and identifies the average crystal sizes of the crystalline materials based on the logarithmic model. The actual average crystal size is then evaluated by electron backscatter diffraction technology for evaluation. The verified results are shown by the filled blocks in FIG. 5. As can be seen from the results, the actual crystal size measured by electron backscatter diffraction technology is included in the 99% confidence interval of the model drawn by the black dotted line, so that the model can be used to evaluate the average crystal size of the crystalline materials to be evaluated, and the prediction result is considered to be very accurate.

[0037] The present invention provides a method for evaluating the crystal size of multiple crystalline materials based on the attenuation of the average power of ultrasonic coda waves. According to the influence of the microscopic structure of multiple crystalline materials on the ultrasonic properties, the ultrasonic coda waves are selected as the measurement signal, and a coda wave time window and a reference time window are respectively selected; JPEG2025016327000028.jpg10170The average power attenuation of the coda wave is obtained through testing, so that the average crystal size of multiple crystalline materials can be detected efficiently. This detection method incorporates the ultrasonic attenuation characteristics and the advantages of detecting coda waves, and can quantify and evaluate the average crystal size of multiple crystalline materials according to the form of the average power attenuation of the coda wave, so that the detection efficiency is high, the measurement robustness is excellent, and the detection result is accurate.

[0038] Finally, it should be noted that the above embodiments are merely for illustrative purposes, and are not intended to limit the technical means of the present invention. Although the present invention has been described in detail with reference to the above embodiments, it is understandable to those skilled in the art that the present invention can still be modified or replaced with equivalents, and any modifications or local replacements that do not deviate from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. Step S1: preparing a number of samples having the same thickness as the multiple crystal materials to be detected, identifying the form and parameters for exciting a signal, and constructing a detection system for the average crystal size of the multiple crystal materials; Step S2, which performs a preliminary process of exciting and receiving ultrasonic signals for samples having different average crystal sizes and band-pass filtering the collected ultrasonic signals; a step S3 of selecting the coda waves, acquiring the average power of each of the selected waves, and calculating the average power attenuation of the coda waves based on the time difference; Step S31, in which the coda wave average power P(t) indicates the energy state of the coda wave portion of the ultrasonic signal at timing t; The equivalent damping coefficient model is calculated as follows: Step S33 shows Step S3, the acquired coda wave time window and the reference time window are located in the coda wave portion and the fundamental wave portion of the ultrasonic signal, and the coda wave portion is selected based on the arrival time of the double shortest boundary wave, and the coda wave signal in the selected coda wave time window has a high signal-to-noise ratio; Among them, θ 1 , θ 2 respectively indicate a model first fitting parameter and a model second fitting parameter, and a step S4 of evaluating the model first fitting parameter and the model second fitting parameter by a least squares method; The average crystal size detection system for a plurality of crystal materials collects and filters ultrasonic signals of a plurality of crystal materials having an unknown crystal size to be detected, and the signals are obtained in step S3. A method for evaluating the crystal size of a plurality of crystalline materials based on the attenuation of the average power of ultrasonic coda waves, comprising:

2. Step S1 Step S11: producing a number of samples having the same chemical composition but different average crystal sizes based on the material component information of the plurality of crystal materials to be detected, and cutting the samples into plate-shaped samples having the same thickness as the plurality of crystal materials to be detected; A step S12 in which an excitation source for exciting an ultrasonic signal is a Hanning window modulated sinusoidal pulse having a single center frequency, and an ultrasonic signal frequency is selected based on elastic property and thickness information for a plurality of crystalline materials to be detected; Step S13: outputting ultrasonic waves through a single channel of the arbitrary function generator, and forming two output terminals through a T-joint, of which the first output terminal is connected to a high-voltage power amplifier, amplified and then transmitted to an excitation ultrasonic transducer wafer, and the second output terminal is directly transmitted to a triggering channel of a mixed signal oscilloscope; Step S14: for each sample, a pair of excitation transducer wafers and receiving transducer wafers having the same center frequency are closely arranged and fixed at the center of the surface of the sample; The method for evaluating the crystal size of multiple crystalline materials based on the attenuation of the average power of ultrasonic coda waves as described in claim 1, further comprising: a step S15 of collecting ultrasonic signals propagating through the sample by a receiving transducer wafer based on the triggering signal received by the triggering channel for each excitation, and transmitting the collected ultrasonic signals to a collecting channel of a mixed signal oscilloscope.

3. Step S2 is Step S21 of randomly cutting out and sampling each sample to obtain an actual crystal size; Step S22: detecting each sample using a pulsed wave configuration, the transducer wafer generating an excitation ultrasonic signal in the sample, and the receiving transducer wafer receiving the ultrasonic signal transmitted in the sample; The method for evaluating the crystal sizes of multiple crystalline materials based on the attenuation of the average power of ultrasonic coda waves as described in claim 1, further comprising a step S23 of repeatedly executing steps S21 and S22 until ultrasonic signals corresponding to samples having different average crystal sizes are obtained, and performing a preliminary process of bandpass filtering the ultrasonic signals.

4. The method for evaluating the crystal size of multiple crystalline materials based on the attenuation of the average power of ultrasonic coda waves as described in claim 1, characterized in that the signal received by the receiving transducer wafer in step S2 is an average value of signals continuously collected 128 times by a mixed signal oscilloscope.

5. 2. The method for evaluating the crystal size of a plurality of crystalline materials based on the attenuation of the average power of ultrasonic coda waves according to claim 1, wherein in step S2, a pulse wave form is adopted to detect the ultrasonic signal in each sample.

6. The method for evaluating the crystal size of a plurality of crystalline materials based on the attenuation of the average power of ultrasonic coda waves according to claim 1, characterized in that in step S21, the actual crystal size d of the sample is quantified via an electron backscatter diffraction technique.

7. In step S1, the average crystal size detection system for the plurality of crystal materials includes an arbitrary function generator, a T-joint, a high-voltage power amplifier, an excitation transducer wafer, a receiving transducer wafer, a mixed signal oscilloscope and an upper controller; The ultrasonic wave is output from a single channel of the arbitrary function generator and transmitted to the Tee joint, the Tee joint has two output terminals, the first output terminal is connected to a high-voltage power amplifier, and is amplified and then transmitted to an excitation ultrasonic transducer wafer, and the second output terminal is directly transmitted to a trigger channel of a mixed signal oscilloscope; The method for evaluating the crystal size of multiple crystalline materials based on the attenuation of the average power of ultrasonic coda waves as described in claim 1, characterized in that the excitation transducer wafer is for generating an excitation ultrasonic signal, and the receiving transducer wafer receives the transmitted ultrasonic signal and transmits the ultrasonic signal to the upper controller.